Strong Mobility Protocol For Mobile Wireless Sensor Networks - Muhammad, Javed (2015)
Wireless Sensor Network (WSN) is a group of locally dispersed and dedicated sensors for monitoring, tracking and recording the physical conditions of the environment and organizing the collecting data at the central location. WSN is basically designed for static sensor network applications, but research has grown from static WSN to mobile WSN applications. However, mobile node and mobile or static coordinators show weaknesses in the standard MAC protocol for WSNs, IEEE 802.15.4 when applied in mobile WSN applications. The aim of this thesis is to overcome the limitations in the IEEE 802.15.4 beacon-enabled MAC protocol in supporting mobile nodes and coordinators in strong mobility. The enhancement in the IEEE 802.15.4 beacon-enabled MAC protocol is implemented in this thesis for mobile WSNs in strong mobility using four different mechanisms. The first mechanism proposed in this thesis is Fast Association Process (FAP) for beacon-enabled IEEE 802.15.4 MAC protocol in mobile WSNs for strong mobility in both mobile nodes and coordinators. FAP is introduced with a new Association_Data request MAC command that increases the association period and provides fast association attempt process in strong mobility. It reduces the redundant service primitives and decreases the association attempt process delay. The second mechanism proposed in this thesis is the Intelligent Coordinator Selection Mechanism (ICSM) which supports the node to select the best coordinators. The proposed mechanism is based on Link Quality Indicator (LQI) values of the received beacon frames from the nearby coordinators. The node selects the coordinator for association that has potential to provide the longest connectivity period. The third mechanism proposed in this thesis is Mobile Node-Controlled Soft handoff (MN-CSHO) mechanism for the IEEE802.15.4 beacon-enabled MAC protocol for mobile WSNs. The proposed MN-CSHO mechanism provides smooth communication to mobile node during coordinator switching process. The last mechanism proposed in this thesis is the enhancement in IEEE802.15.4 beacon-enabled MAC protocol to reduce delay in transmission of critical data. It is achieved by suggesting appropriate beacon order (BO), superframe order (SO) values and proposed modified superframe structure for the IEEE 802.15.4 beacon-enabled MAC protocol in both static and mobile WSN applications. Hence, the research contributes for the maximization of network performance, throughput, higher node speed and association period and minimization of energy consumption, packet loss, delay in association attempt process and disassociation period.